Phytochemical Profile and Biological Activities of the Extracts from Two Oenanthe Species (O. aquatica and O. silaifolia) - Łukasz Świątek; Elwira Sieniawska; Mohamad Fawzi Mahomoodally; Nabeelah Bibi Sadeer; Krzysztof Kamil Wojtanowski; Barbara Rajtar; Małgorzata Polz-Dacewicz; Mehmet Yavuz Paksoy; Gokhan Zengin (MDPI AG, 2021)
This study presents the evaluation of biological activities and chemical profiling of Oenanthe aquatica (L.) Poir. and Oenanthe silaifolia M. Bieb. The phytochemical profile, antioxidant, enzyme inhibitory, cytotoxic and antiviral activities of the methanolic and aqueous extracts were investigated. The aqueous extract of O. aquatica possessing the highest content of phenolics (60.85 mg gallic acid equivalent/g extract), also exhibited the strongest radical scavenging potential against 2,2-diphenyl-1-picrylhydrazyl and 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (79.46 and 148.66 mg Trolox equivalent/g extract, respectively), the highest reducing ability (207.59 and 107.27 mg Trolox equivalent/g extract, for cupric reducing antioxidant capacity and ferric reducing antioxidant activity, respectively), metal chelating potential (33.91 mg ethylenediaminetetraacetic acid equivalent/g extract) and total antioxidant ability (1.60 mmol Trolox equivalent/g extract). Liquid chromatography-electrospray ionization-quadrupole time-of-flight-mass spectrometry (LC-ESI-QTOF-MS/MS) permitted tentative identification of compounds from simple organic acids, phenolic acids, coumarins, flavonoids and their glycosides in O. aquatica and O. silaifolia extracts. The methanolic extract of O. aquatica substantially depressed acetylcholinesterase (3.67 mg galantamine equivalent/g extract), tyrosinase (126.66 mg kojic acid equivalent/g extract), and α-amylase (0.83 mmol acarbose equivalent/g extract) enzymes. The methanolic extract of O. silaifolia showed highest enzymatic inhibitory property against butyrylcholinesterase, and its aqueous extract depressed α-glucosidase activity (0.26 mmol acarbose equivalent/g extract). All tested extracts exerted selective toxicity towards cancer cell lines, and the highest anticancer potential was found for O. aquatica aqueous extract on FaDu and HeLa cells with CC50 of 57.36 and 47.16 µg/mL, respectively. Significant antiviral activity against HSV-1 (HHV-1) was found for both aqueous extracts in concentrations of 1000 µg/mL, which inhibited the HSV-1 cytopathic effect (CPE) in virus infected VERO cells and reduced the virus infective titer by more than 3 log (logCCID50/mL). This study has produced critical scientific data on O. aquatica and O. silaifolia, which are potential contenders for the development of novel phyto-pharmaceuticals.